2007
DOI: 10.1002/jmv.20829
|View full text |Cite
|
Sign up to set email alerts
|

Presence, quantitation and characterization of JC virus in the urine of Italian immunocompetent subjects

Abstract: Human polyomavirus JC (JCV) infects the worldwide population, remains latent in the kidney, and is excreted in the urine. A longitudinal study was performed in order to evaluate JCV excretion, to characterize molecularly the virus and to determine if its presence in urine is a consequence of viral reactivation or merely of epithelial squamous cell shedding. The presence of cellular sediment and the JCV genome were examined in 333 urine samples collected periodically for 3 months from 17 healthy subjects; molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 25 publications
6
35
1
Order By: Relevance
“…This study confirmed previous results that demonstrated how subtype I was predominant in urine samples obtained from patients with bone marrow transplants and hemorrhagic cystitis . The epidemiology of JC virus shows that genotype I is the most common JC virus circulating in Europe and the genome detected most frequently in the Italian population [Stoner et al, 2000;Agostini et al, 2001a;Pagani et al, 2003;Rossi et al, 2007]. In these seven patients, the JC genotype IA was detected in co-infected individuals, whereas in patient no.…”
Section: Discussionmentioning
confidence: 85%
“…This study confirmed previous results that demonstrated how subtype I was predominant in urine samples obtained from patients with bone marrow transplants and hemorrhagic cystitis . The epidemiology of JC virus shows that genotype I is the most common JC virus circulating in Europe and the genome detected most frequently in the Italian population [Stoner et al, 2000;Agostini et al, 2001a;Pagani et al, 2003;Rossi et al, 2007]. In these seven patients, the JC genotype IA was detected in co-infected individuals, whereas in patient no.…”
Section: Discussionmentioning
confidence: 85%
“…The genetic structure of RR directly affects viral transcription and replication by change the level of DNA/protein and cofactors binding sites, thus leading to distinct cellular tropism 6 . The urinary shedding of JCV with archetype structure is frequent among healthy and immunocompromised individuals 7,8,9,10 , but rearranged forms with deletions, insertions and duplications are usually found in viruses from blood and brain of patients with PML 11,12 . Much less frequently, the rearranged form of JCV can be found in the urine of patients experiencing asymptomatic reactivation 13 .…”
Section: A Short Background Of Pmlmentioning
confidence: 99%
“…JCV excretion in the urine can reach 46% in immunocompetent patients, and the virus usually remains asymptomatic [Pagani et al, 2003;Rossi et al, 2007]. However, reactivation of either virus in immunosuppressed patients can cause several clinical syndromes.…”
Section: Introductionmentioning
confidence: 98%